Growth, Yield and Bulb Quality as Affected by Nitrogen Fertilization and Intra-row Spacing of Two Onion (Allium cepa L.) Cultivars (University of Khartoum Journal of Agricultural Sciences, 2022)
In response to the rising demand and escalating prices due to several internal demographic reasons in the last few years, interest in increasing productivity and bulb quality has been a major concern. The objective of this research was,therefore, to improve yield and quality of onion through determining more relevant and contemporary nitrogen and population density that cope with the changing production environment in Sudan. So an experiment to study the effect of threenitrogen fertilization levels (0, 120 and 240 kg N/ha.) and three population densities (intra-row spacing of 5, 10 and 15 Cm) on growth, yield and quality of two widely consumed cultivars [Kamlin and Texas Early Grano(TEG)] was carried out for twoseasons. Treatments were arranged in a split-split plot design with three replications; cultivars were randomized in the main plots, intra-row spacing in the sub-plots and nitrogen fertilization in the sub-sub plots. Results indicated that nitrogen applicationat the rate of 120 kg N/ha significantly increased vegetative growth, bulb size, total and marketable yields. Moreover, bolting percentage (a main quality defect) decreased with increasing nitrogen fertilization. Nitrogen fertilization had nosignificant effect on bulb shape, dry matter and TSS. Although high plant density (5cm intra-row spacing) reduced plant growth and increased bolting, it also increased total and marketable yields and reduced bulb splitting (a defect). CultivarTEG exceeded Kamlin in plant growth aspects and consequently average bulb weight, total and marketable yields; however, bulb splitting was also high. In conclusion, planting onion at 5cm intra-row spacing and applying 120 kg N/ha., significantly increased productivity and improved bulb quality in central Sudan.
Keywords: Allium cepa L.; vegetable crops; bolting; N fertilization; intra-row spacing; cultural practices